Grammatical Analysis of Students’ Narrative Writing - Fitriyeni Fitriyeni (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
In foreign language learning, grammar is a crucial element in communication, and without the correct organization of grammar, language exchange is intruded. This study explored grammatical issues in students’ narrative writing. Data were collected from students’ narrative writing products that belonging to an English One class of the Accounting Diploma III Program of Bina Sarana Informatika University, Jakarta, Indonesia. The collected data were analyzed to examine grammatical issues encountered by the students using Dulay (1982) surface strategy taxonomy, which covers omission, addition, misinformation, and misordering errors; and Sadiah and Royani (2019) for verb of tenses, punctuation and preposition. Results showed there were totally 51 grammatical errors identified in the students’ writing products, specifically, existed 30 errors of others, 8 omission errors, 6 misinformation errors, 4 misordering errors, and 3 addition errors. It is expected that the findings can assist teachers and learners in overcoming grammatical issues, so that the teachers can use better solutions in teaching grammar and the learners can improve their English grammar and writing skills.